The advantage of ultrasound during electrodeposition on morphology and corrosion stability of Zn-Co alloy coatings. (3rd May 2020) - Riđošić, M.; García-Lecina, E.; Salicio-Paz, A.; Bajat, J.
ABSTRACT: The influence of ultrasound agitation on the properties of electrodeposited Zn-Co coatings was analysed and compared with coatings deposited by using magnetic stirring. The morphology and chemical composition of the deposits were analysed by scanning electron microscopy coupled with energy dispersive X-ray spectroscopy. X-ray diffraction was used in examining the crystallographic orientation and phase composition of the coatings. It was found that utilising ultrasound during deposition enhanced the compactness, homogeneity and corrosion resistance of the coatings compared to deposition with magnetic stirring of the plating solution. Magnetically stirred coatings were dendritic and porous, whereas coatings produced under ultrasound agitation were more homogeneous and dense. The higher the ultrasound intensity applied the higher the cobalt content in the coating. The corrosion resistance of Zn-Co coatings was improved by ultrasound agitation, with the best results obtained at 20 W cm −2 of ultrasound intensity.